Comparison of the Hybrid Capture II Assay With the Human Papillomavirus DNA Chip Test for the Detection of High-Grade Cervical Lesions. Issue 5 (1st July 2009) - Kang, Woo Dae; Kim, Cheol Hong; Cho, Moon Kyoung; Kim, Jong Woon; Kim, Yoon Ha; Choi, Ho Sun; Kim, Seok Mo
Abstract : Cervical intraepithelial neoplasia (CIN) 2 is used as the threshold for treatment decisions. This study was conducted to evaluate the clinical efficacy of the Hybrid Capture II assay (HC2) and the human papillomavirus (HPV) DNA chip test (HDC) for detecting HPV in high-grade cervical lesions CIN2 or greater, including adenocarcinoma (CIN2+). Seven hundred forty-one women with abnormal cervical cytology were evaluated with the HC2, the HDC, and histological assessment of the cervix. The overall agreement of the 2 HPV tests was 88.8% ( κ value, 0.61). Of 615 high-risk HPV-positive specimens by the HC2, 571 (92.8%) were HDC-positive. Both tests were performed similarly on CIN2+ samples; the sensitivities of the HC2 and HDC as predictors of CIN2+ were 93.4 and 92.6%, respectively. In 83 cases of discrepancies between the HC2 and HDC, genotyping of 39 HC2-negative/HDC-positive cases revealed 13 HPV-53, 8 HPV-58, 7 HPV-16, 6 HPV-18, 2 HPV-68, 1 HPV-31, 1 HPV-45, and 1 HPV-66. In 515 patients with CIN2+, HPV-16 (45.0%) was the most common type; the next most common types were HPV-58 (20.8%), HPV-18 (16.1%), HPV-31 (6.6%), and HPV-33 (6.6%). Human papillomavirus types 16, 58, and 18 were more likely associated with CIN2+ ( P < 0.05). In conclusion, the HDC is a reliable diagnostic tool for the detection of CIN2+. In addition, the HDC provides useful information regarding viral genotypes.